2018
DOI: 10.1039/c8cc02794c
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of a high-performance titanosilicate catalyst with controllable defective Ti(OSi)3OH sites

Abstract: A novel TS-1 (TS-1S) catalyst with newly-generated defects, i.e. Ti(OSi)3OH species, which exhibits the highest reactivity among different Ti species, is constructed in an ingenious strategy. This also provides a promising way to effectively tune the intrinsic nature of Ti active centres in other titanosilicates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 34 publications
2
65
0
Order By: Relevance
“…The IR spectra in the hydroxyl region (Fig. 4c) demonstrated that HCS-TS had more Ti-OH groups, with an obvious absorption band at 3676 cm À1 , whereas it was difficult to be detected in TS-1 and H-TS-1, 22 consistent with the peak of 235 nm formed in UV-vis spectra. Furthermore, the absorption band at 3500 cm À1 was attributed to hydrogen-bonded silanol nests.…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…The IR spectra in the hydroxyl region (Fig. 4c) demonstrated that HCS-TS had more Ti-OH groups, with an obvious absorption band at 3676 cm À1 , whereas it was difficult to be detected in TS-1 and H-TS-1, 22 consistent with the peak of 235 nm formed in UV-vis spectra. Furthermore, the absorption band at 3500 cm À1 was attributed to hydrogen-bonded silanol nests.…”
Section: Resultssupporting
confidence: 61%
“…5D ). 22,25,45,49 The above results implied the existence of open tetra-coordinated titanium (Ti(OSi) 3 OH) species in HCS-TS. 22 …”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations